CORPORATE SOCIAL RESPONSIBILITY DAN TANGGUNG JAWAB NEGARA TERHADAP HAK EKONOMI, SOSIAL, DAN BUDAYA DI INDONESIA - Sefriani Sefriani; Sri Wartini (Faculty of Law, Universitas Sebelas Maret, 2015)
AbstractIndonesia has enacted the idea of corporate social responsibility (CSR) into the laws as a liability which bears sanctions. It is uncommon practice. The majority of state’s practices are putting CSR as a voluntary issue on the law instead of treating it as a liability which holds sanctions. Such enactment give rise allegation against the state which accusing it for transferring its obligation to fulfill the economic, social and culture rights (ESCR) to the company in the format of CSR. Indonesia has some arguments to justify such enactment such as 75% environmental destruction and social problems in Indonesia caused by company activities; the company is able to violate human rights even worse than other legal subject can do; the law which possess voluntary characteristic was ineffective in Indonesia since the legal culture and the awareness concerning the importance of CSR is still not quite; provide legal certainty and avoid inconstant interpretation upon CSR which might be conducted by company by elevating business ethic become legal norm; and integrate social, moral and law issue since three of them inseparable. The enactment of CSR as liability which hold sanction by Indonesia is not a form of transferring the state responsibility to corporate, however it is a manifestation of Indonesian government seriousness as the primary duty bearer, to perform its obligation concerning ESCR through effective legislation since the corporates activities are directly related to the enjoyment of the rights enshrined in the ICESCR. Allegation on the transfer of state obligation on to the company will be proved if the state is hands off and diverting its entire obligation to fulfill ESCR to company in the format of CSR program. AbstrakIndonesia menormakan tanggung jawab social dan lingkungan (TJSL/CSR) dalam perundang- undangannya sebagai suatu kewajiban yang disertai sanksi. Suatu praktek yang tidak lazim dengan praktek Negara pada umumnya yang menormakannya sebagai kesukarelaan perusahaan bukan kewajiban apalgi disertai sanksi. Hal ini menimbulkan kecurigaan bahwa Negara hendak mengalihkan tanggung jawab pemenuhan hak ekonomi, social dan budaya (ekosob)-nya kepada perusahaan yang dikemas dalam bentuk kewajiban CSR. Penormaan CSR dalam bentuk kewajiban yang disertai sanksi sesungguhnya merupakan bukti keseriusan Indonesia melaksanakan tanggung jawab hak ekosobnya melalui penglegislasian yang mengikat karena budaya hukum di Indonesia belum memungkinkan untuk membuat aturan yang sifatnya sukarela. Penormaan CSR sebagai suatu kewjaiban disertai sanksi tidak akan menghilangkan karakteristiknya sebagai social responsibility karena hukum tidak bisa dipisahkan dari social dan moral. Masalah kerusakan alam dan masalah social yang ditimbulkan perusahaan sudah sangat besar di Indonesia, dan pengalaman menunjukkan perusahaan mampu melakukan pelanggaran HAM yang jauh lebih hebat dari yang dilakukan subyek hukum lain menjadi justifikasi bahwa penormaan yang sifatnya mengikat sangatlah diperlukan. Kecurigaan adanya modus pengalihkan tanggung jawab ekosob pada perusahaan akan terbukti bila Negara kemudian lepas tangan dan membebankan sepenuhnya tanggung jawab pemenuhan hak ekosob pada perusahaan melalui program CSR. Apabila itu terjadi maka Negara telah melakukan pelanggaran terhadap kewajiban hak ekosobnya mengingat Indonesia telah meratifikasi International Covenant on Economic Social Culture Right sejak tahun 2005 melalui UU No.11 Tahun 2005.